2022
DOI: 10.3390/ani12030280
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Rearing Enrichments on Pullets’ and Free-Range Hens’ Positive Behaviors across the Flock Cycle

Abstract: Enrichment during the indoor rearing of pullets destined for free-range systems may optimize pullet development including increasing motivated natural behaviors (termed ‘positive behaviors’) including foraging, dust bathing and chick play. Hy-Line Brown® chicks (n = 1700) were floor-reared indoors across 16 weeks with three enrichment treatments (n = 3 pens/treatment): (1) standard control, (2) weekly novel objects—‘novelty’, (3) perching/navigation structures—‘structural’. At 16 weeks, pullets (n = 1386) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The adult hens retained rearing enrichment differences through to the end of the production cycle, although the specific phylogenetic groups that differed changed across the pullet and adult sampling points. In accordance with these microbiota differences, the rearing treatments had long-term impacts on other behavior, welfare, and egg quality measures in the birds (Bari et al, 2020a(Bari et al, ,b,c, 2021Campbell et al, 2020bCampbell et al, , 2022, although not on the short-chain fatty acids analyzed in the current study. These enrichment treatment differences support sustained effects of rearing environments regardless of the similar housing conditions experienced as adults.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The adult hens retained rearing enrichment differences through to the end of the production cycle, although the specific phylogenetic groups that differed changed across the pullet and adult sampling points. In accordance with these microbiota differences, the rearing treatments had long-term impacts on other behavior, welfare, and egg quality measures in the birds (Bari et al, 2020a(Bari et al, ,b,c, 2021Campbell et al, 2020bCampbell et al, , 2022, although not on the short-chain fatty acids analyzed in the current study. These enrichment treatment differences support sustained effects of rearing environments regardless of the similar housing conditions experienced as adults.…”
Section: Discussionsupporting
confidence: 70%
“…Recent evidence from pigs, reported that enriched housing affected microbiota colonization relative to standard control housing (Wen et al, 2021), although this effect was not confirmed across other research (Saladrigas-García et al, 2021). The inclusion of enrichment in the pens resulted in some variation across the rearing period in exhibited behaviors (Campbell et al, 2022), responses to fear tests (Campbell et al, 2021), and body weight (Campbell et al, 2020c). In the week following the sample collection when the pullets were transferred to the laying facility, there were also rearing treatment differences in perching behavior in the new pens (Campbell et al, 2020c).…”
Section: Discussionmentioning
confidence: 93%
“…(2020) detected no difference in the amount of spontaneous play performed by broilers (running with or without wing-use, stationary wing flapping, sparring). In addition, no difference in play levels (recorded as in Liu et al., 2020 ) were found between young layer pullets given novel objects each week or provided with perching structures compared to those in control pens ( Campbell et al, 2022 ). In female turkey poults, provision of a “turkey tree” comprising platforms at different heights resulted in levels of wing-assisted running comparable to the control ( Lindenwald et al, 2021 ).…”
Section: Playful Poultry: What Does It Take and What Does It Mean?mentioning
confidence: 92%
“…When performed in a playful context, these behaviors represent object, locomotory, and social play, respectively. Play behavior is seen in Red Junglefowl ( Kruijt, 1964 ), domestic broilers, and layer chickens ( Dawson and Siegel, 1967 ; Cloutier et al, 2004 ; Baxter et al, 2019 ; Campbell et al, 2022 ), as well as in turkeys ( Hale and Schein, 1962 ). Play can also be seen in other poultry species, but reports are lacking.…”
Section: Playful Poultry: What Does It Take and What Does It Mean?mentioning
confidence: 99%
“…Exploration and foraging all [28,33,34] broilers [30,[39][40][41][42][43][44][45][46][47][48][49][50] laying hens [51][52][53] turkeys [54,55] ducks [56] geese [57] Comfort general all [27][28][29]34] dustbathing broilers [42,49,58,59] laying hens [31,51,52,[60][61][62][63][64] quails [65] preening all [28,33,34] broilers [40,41,44,58] laying hens [31,52,61,66,…”
Section: Behavioral Parametersmentioning
confidence: 99%